An Old Dog with New Tricks – Additions to the Cesium Lithium Chloride System: Cs3Li2Cl5 and the Hydrated Cs3LiCl4·4H2O. Issue 30 (7th August 2019) - Ortner, Teresa S.; Scheifers, Jan P.; Flores, Justin; Zhang, Yuemei; Iyer, Abishek K.; Gesing, Thorsten M.; Fokwa, Boniface P. T.
Abstract : The CsCl/LiCl system has been studied for over a century now. Numerous phases have been predicted – only three have hitherto been found. We present the synthesis and single‐crystal structure of the cesium lithium pentachloride Cs3 Li2 Cl5, predicted earlier but with a different structure. The anhydrous new phase readily reacts to Cs3 LiCl4 · 4H2 O in air. The tetrahydrate can also be obtained through the simplest, most inexpensive and green synthesis possible: an immediate, room‐temperature mechanosynthesis from only CsCl and LiCl (3:1) in air. Differential scanning calorimetry (DSC) and thermogravimetric analyses (TGA), as well as in situ temperature‐dependent powder X‐ray diffraction studies on this second ever reported ternary alkali chloride hydrate allowed for a revision of the CsCl/LiCl phase diagram. Density of states and total energy calculations further elucidate the new alkali chlorides and update the relative stability of previous structure predictions. Abstract : Never say never! We report on the CsCl/LiCl system, studied for over a century now, with still only three members characterized. We present Cs3 Li2 Cl5, predicted to have a different structure; and the second ever found ternary alkali chloride hydrate, Cs3 LiCl4 · 4H2 O, discovered through the most inexpensive and green synthesis possible: a room‐temperature mechanosynthesis from the binary salts. Consequently, we revise the CsCl/LiCl phase diagram.